Effects of a randomized controlled trial of a brief, student-nurse led, parent-based sexual health intervention on parental protective factors and HPV vaccination uptake - D. Santa Maria; C. Markham; S. M. Misra; D. C. Coleman; M. Lyons; C. Desormeaux; S. Cron; V. Guilamo-Ramos (BMC, 2021)
Abstract Background Parents play a pivotal role in adolescent sexual health and Human Papillomavirus (HPV) vaccination. Nurses are on the frontlines of healthcare and play a critical role in promoting HPV vaccination and parent-child sexual health communication. We enhanced the Families Talking Together (FTT) parent-based sexual health curriculum to include adolescent vaccinations herein, FTT + HPV, and trained student nurses to provide a strong HPV vaccination and parent-child sexual health communication endorsement. Methods Using a randomized attention-controlled trial design, we examined the efficacy of FTT + HPV among 519 parents and their 11-14 year old youth recruited from medically underserved communities between 2015 and 2018. Participants were recruited from 22 after-school programs (e.g., Boys and Girls Clubs) and 19 charter schools. For parents, we examined protective factors including parent-child sexual health communication and parental involvement. For youth, we examined sexual health knowledge, parent-child sexual health communication, and parent-child connectedness. To assess HPV vaccination initiation and completion, we searched IMMTRAC immunization registry records for 85% of youth and used parental report for youth without registry records. Group differences were calculated using the estimated mean difference at one- and six months post-intervention with significance set at the p < 0.05 level. Results Baseline rates of HPV vaccination were low at 55.7%. No significant difference between the groups was seen in vaccination initiation or completion rates by one-month post-intervention. However, by six-months post intervention, there was a significant difference between the groups with 70.3% of the intervention group initiating the HPV vaccination series vs. 60.6% for the control group (p = 0.02). No difference between the groups was found for HPV series completion at six-months. There were significant differences in condom knowledge (p = 0.04), parent-child connectedness (p = 0.04), and communication frequency (p = 0.001) with greater improvement in the intervention vs. the control group. Rates of sexual activity remained low in both groups throughout the six-month follow-up period. Conclusion A brief parent-based adolescent sexual health and HPV vaccination intervention delivered by student nurses can improve sexual health outcomes including protective parental factors, adolescent sexual health knowledge, and HPV vaccination initiation rates. Trial registration ClinicalTrials.gov Identifier: NCT02600884 . Prospectively registered September 1, 2015.